2017
DOI: 10.1021/acs.est.6b04821
|View full text |Cite
|
Sign up to set email alerts
|

Toward Financially Viable Phytoextraction and Production of Plant-Based Palladium Catalysts

Abstract: Although a promising technique, phytoextraction has yet to see significant commercialization. Major limitations include metal uptake rates and subsequent processing costs. However, it has been shown that liquid-culture-grown Arabidopsis can take up and store palladium as nanoparticles. The processed plant biomass has catalytic activity comparable to that of commercially available catalysts, creating a product of higher value than extracted bulk metal. We demonstrate that the minimum level of palladium in Arabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 37 publications
(69 reference statements)
0
50
0
Order By: Relevance
“…Miscanthus and 16 willow species and cultivars were tested in a palladium-contaminated synthetic and minesourced tailings. The results indicated the possibility of using the plants for accumulating palladium and decreasing the overall environmental impacts associated with its extraction [153].…”
Section: Resultsmentioning
confidence: 91%
“…Miscanthus and 16 willow species and cultivars were tested in a palladium-contaminated synthetic and minesourced tailings. The results indicated the possibility of using the plants for accumulating palladium and decreasing the overall environmental impacts associated with its extraction [153].…”
Section: Resultsmentioning
confidence: 91%
“…However, such systems have struggled to be commercially viable . It has recently been demonstrated that palladium on carbon catalysts from plants (produced through phytomining) are worth five times more than the value of the pure metal . Using nanoparticles in planta adds value and reduces energy inputs and processing costs for the production of catalysts .…”
Section: Recovery Of Elementsmentioning
confidence: 99%
“…It has recently been demonstrated that palladium on carbon catalysts from plants (produced through phytomining) are worth five times more than the value of the pure metal . Using nanoparticles in planta adds value and reduces energy inputs and processing costs for the production of catalysts . Although the use of the plant after metal uptake has been demonstrated as an effective material for the production of catalysts, the thermal treatment of the metal‐laden biomass could also generate bio‐based chemicals as part of a biorefinery.…”
Section: Recovery Of Elementsmentioning
confidence: 99%
“…A promising disposal method for metal-enriched hazardous waste is upcycling in the form of high value-added products (Harumain et al, 2017;Cui et al, 2018;Ye et al, 2019). In principle, noble metals (e.g., Ni, Au, Cu, and Pt) can be directly recovered by incineration/pyrolysis or leaching (Keller et al, 2005;Zhang et al, 2014;Guilpain et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, Cd is not a valuable heavy metal, and it is not economically viable to extract it directly from Cd-accumulated hazardous waste (Sadegh et al, 2007;Chen et al, 2019c). Interestingly, some metal-enriched hazardous wastes have shown great potential for upcycling as catalysts (Parker et al, 2014;Harumain et al, 2017;Chen et al, 2019c,d). For example, palladium in metal-enriched hazardous wastes can be recovered in the form of high-value carbonsupported catalysts (Parker et al, 2014;Harumain et al, 2017).…”
Section: Introductionmentioning
confidence: 99%